Revolutionizing Drug Delivery and Therapeutics: The Biomedical Applications of Conductive Polymers and Composites-Based Systems - Sharanya Paramshetti; Mohit Angolkar; Adel Al Fatease; Sultan M. Alshahrani; Umme Hani; Ankitha Garg; Gundawar Ravi; Riyaz Ali M. Osmani (MDPI AG, 2023)
The first conductive polymers (CPs) were developed during the 1970s as a unique class of organic substances with properties that are electrically and optically comparable to those of inorganic semiconductors and metals while also exhibiting the desirable traits of conventional polymers. CPs have become a subject of intensive research due to their exceptional qualities, such as high mechanical and optical properties, tunable electrical characteristics, ease of synthesis and fabrication, and higher environmental stability than traditional inorganic materials. Although conducting polymers have several limitations in their pure state, coupling with other materials helps overcome these drawbacks. Owing to the fact that various types of tissues are responsive to stimuli and electrical fields has made these smart biomaterials attractive for a range of medical and biological applications. For various applications, including the delivery of drugs, biosensors, biomedical implants, and tissue engineering, electrical CPs and composites have attracted significant interest in both research and industry. These bimodalities can be programmed to respond to both internal and external stimuli. Additionally, these smart biomaterials have the ability to deliver drugs in various concentrations and at an extensive range. This review briefly discusses the commonly used CPs, composites, and their synthesis processes. Further highlights the importance of these materials in drug delivery along with their applicability in various delivery systems.